Transcriptomics and quantitative proteomics reveal changes after second stimulation of bone marrow-derived macrophages from lupus-prone MRL/lpr mice - Chen, Keyue; Wu, Tiyun; Wang, Danyan; Li, Rong; Shen, Xiangfeng; Zhao, Ting; Ozato, Keiko; Li, Rongqun (Frontiers in Immunology, 2022)
Innate immune memory can cause the occurrence and exacerbation of autoimmune diseases, and it is as well as being strongly associated with the pathogenesis of systemic lupus erythematosus (SLE), however, the specific mechanism remains to be further studied. We learned that IFN-γ stimulation generated innate immune memory in bone marrow-derived macrophages (BMDMs) and activated memory interferon-stimulated genes (ISGs). This research used IFN-γ and lipopolysaccharide (LPS) to treat BMDMs with lupus-prone MRL/lpr mice and showed that particular memory ISGs were substantially elevated in prestimulated macrophages. In order to identify the differentially expressed genes (DEGs), researchers turned to RNA-seq. GO and KEGG analysis showed that up-regulated DEGs were enriched in defense and innate immune responses, and were related to the expression of pattern recognition receptors (PRRs)-related pathways in macrophages. TMT-based proteome analysis revealed differentially expressed proteins (DEPs) up-regulated in BMDMs were abundant in metabolic pathways such as glucose metabolism. Our study found that after the secondary stimulation of MRL/lpr mice, the expression of PRRs in innate immune cells was changed, and IFN-related pathways were activated to release a large number of ISGs to promote the secondary response. At the same time, related metabolic modes such as glycolysis were enhanced to regulate epigenetic changes. Therefore, SLE is brought on, maintained, and worsened by a variety of factors that work together to produce innate immune memory.